MULTIMEDIA INTERAKTIF MATEMATIKA MATERI PECAHAN PADA SDIT FAJAR ILAHI 2 - Siahaan, Arta Uly; Fitri, Lailatul; Neta, Fandy (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2019)
The developmet of technology are increasingly advanced changing aspects of education for the students’ teaching and learning process. Based on the 2013 curriculum in mathematics learning for SDIT Fajar Ilahi 2 class IV there are fraction materials. The subject matter of mathematics learning in school is still less interesting with learning method such as lectures. This interactive multimedia fraction material is used as an alternative learning media equipped with fractions in the form of text, images, and animations. The interactive multimedia is made using the MDLC (Multimedia Development Life Cycle) method with 6 stages. Namely concept, design, material collecting, assembly, testing, and distribution. The interactive multimedia testing consists of validating media experts and material experts, testing normality, and testing paired sampel t-tests. The results of the interactive multimedia material fractions with the assessment of media experts get 89,7% percentage in the category of very decent. The assessment from material experts get a percentage of 94,81% in the very feasible category. While the paired sample t-test found a significance value of 0,000 < 0,05, the use of interactive multimedia fraction material is very useful in grade IV elementary school. It is clear that this product can achieve the objcetives of this research.